Calixarene Complexes: Synthesis, Properties and Applications - Berberan-Santos, Mario; Marcos, Paula M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
A growing interest has been devoted to the development of host systems for ionic and neutral species based on calixarenes. These cyclic oligomers show important host-guest properties, which has led to numerous applications in a broad range of fields, including organocatalysis, sensing, extraction and separation, and, more recently, biomedical applications. The relative ease of the functionalization of their upper and lower rims and the presence of a pre-organized cavity that is available in different sizes and conformations make calixarenes attractive building blocks for the construction of supramolecular assemblies. This book presents the most recent developments on the host-guest properties of calixarenes, as well as the new synthetic methods and applications.